1960
DOI: 10.2136/sssaj1960.03615995002400060021x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Various Particle‐Size Fractions of Limestone

Abstract: The relative efficiency of various fractions of a calcitic limestone was studied under greenhouse conditions. Pure calcium carbonate, a commercial sample of agricultural limestone, and 6 particle‐size fractions separated from this commercial sample were applied at different rates to 3 acid soils. The soils were sampled at various times and the pH determined. The changes in pH with time followed an expression of the form, pHf = pHo + b Log (1 + t). The factor b varied with rate of application, particle size, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

1968
1968
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
0
9
0
4
Order By: Relevance
“…Similarly, Morrison et al (1989) found that coralline lime was a good amendment for Fijian soils, provided that the lime was sufficiently fine. Such a finding is readily understood, given the fact that CaCO2 particles > 2 mm dissolve much slower than particles < 0.25 mm (Motto and Melsted, 1960).…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, Morrison et al (1989) found that coralline lime was a good amendment for Fijian soils, provided that the lime was sufficiently fine. Such a finding is readily understood, given the fact that CaCO2 particles > 2 mm dissolve much slower than particles < 0.25 mm (Motto and Melsted, 1960).…”
Section: Introductionmentioning
confidence: 97%
“…Admitindo-se correta a conclusão de conhecidos trabalhos sobre efeitos de calcário em solos ácidos (2,6,7,8) ; de que partículas com diâmetros superiores a 0,8 mm têm pouco ou nenhum efeito corretivo do solo, poder-se-ia chegar à indicação de que grande parte dos pós calcários comercializados em São Paulo apresentam 20% a 30% de material ineficiente como corretivo do solo.…”
Section: -Discussão E Conclusõesunclassified
“…Numerosas investigações, realizadas com a finalidade de verificar o valor agrícola dos calcários, em função de diferentes graus de finura, e levadas a efeito tanto por meio de ensaios em terras ácidas (2,3,6,7,8) como por meio de processos químicos em laboratório (4,5,9,10,12), mostraram que quanto mais fino fôr o material empregado, maior e mais rápida será a sua ação corretiva de acidez dos solos. Subsistem dúvidas quanto à eficiência das partículas mais grosseiras.…”
Section: -Introduçãounclassified
See 1 more Smart Citation
“…That same piece of limestone ground so that each particle is the exact size to just pass a 0.15 mm screen (100-mesh), and assuming that these particles remain perfect cubes, would have an increased flat surface area approximating 983 cm 2 . Motto and Melsted [6] showed that particles in the 2.0-to 0.85-mm (20 mesh) fraction were 14% as effective as those in the 0.15-mm (100 mesh) fraction, and particles larger than 2 mm were essentially of no value. [1] On soils very low in CEC, some slow release (relatively large particles) may extend the time the pH change will last before reapplication of limestone is necessary.…”
Section: Introductionmentioning
confidence: 99%